MARPE for the treatment and cure of OSAS: Aruba experience - Kawaiah, Abdal Hadi; Kondepati, Ananda Kumar; Pasumarthi, Shalini Devaprasad; Mishra, Tulika; Singh, Pratik Kumar; Nijhar, Pukhraj Singh (Asian Journal of Medical Sciences, 2020)
Obstructive sleep apnea syndrome (OSAS) is defined as “the stoppage of ventilation or incidence of significant hypoventilation during sleep, which is characterized by episodes of partial or complete upper airway obstruction related with hypoxemia and/or hypercarbia. There have been many treatments reported for this syndrome including Mandibular repositioning appliance (MRA), continuous positive airway pressure (CPAP), weight loss, exercise, intraoral appliance therapy, soft tissue procedures, and maxillomandibular advancement (MMA) surgery. Present study is an attempt where three patients of OSAS have been treated with Miniscrew-assisted rapid palatal expansion (MARPE). The results of BMI, AHI index showed the promising effect. Even the use of MARPE has improved the air flow and increased the rapid palatal area.